Anti-obesity activity of polyherbal formulation Divya-Medohar-Vati by inhibition of pancreatic lipase activity and triglyceride translocation through enterocytes - Acharya Balkrishna; Anamica Singh; Jagdeep Singh; Subarna Pokhrel; Kunal Bhattacharya; Anurag Varshney (Elsevier, 2022)
Background: Obesity is a modern-day epidemic affecting human lifestyle worldwide and originates from high fat-content food consumption. Traditional Ayurveda-based polyherbal medicine 'Divya-Medohar-Vati' (DMV) has been recommended as an anti-obesity formulation. Methods: In the present study, we explored the anti-obesity activity of DMV using biochemical assay, simulated gastrointestinal tract (GIT) digestion model, and Caco-2-derived enterocyte model. We further correlated the observed biological activity of DMV with its phytochemical profile determined using the high-performance-liquid-chromatography method. Results: Phytochemicals such as Gallic acid, Ellagic acid, Chebulic acid, Picroside I, and Arjungenin were identified in DMV. DMV and 'Orlistat' (positive control) showed half-maximal inhibitory concentrations (IC50) of 647.88 and 21.80 µg/ ml, respectively against porcine pancreatic lipase activity. Addition of DMV and Orlistat to full cream during simulated GIT digestion reduced the hydrolysis of triglyceride into long-chain Palmitic acids and glycerol molecules in obtained digestae. At the same time, both DMV and Orlistat stimulated the release of medium-chained Capric acids in full cream digestae. Treatment of enterocytes with DMV-induced a loss of cell viability (IC50 at 308.5 μg/ml). Translocation of re-esterified triglycerides by enterocytes grown on transwell plate following treatment with full cream digestae was inhibited after the addition of DMV and Orlistat. Conclusions: Taken together, DMV showed good inhibition for pancreatic lipase activity, and hydrolysis of triglycerides modulating the release of free glycerol and dietary fatty acid (Capric acid and Palmitic acid) contents. DMV also reduces the translocation of triglycerides through the basal region of enterocytes. Hence, Divya-Medohar-Vati was found to be an effective anti-obesity polyherbal formulation.